The Implementation of Role of Kuttab Al-Fatih (KAF) Philosophy in Islamic Character Education - Hafnidar Hafnidar; Rosnidar Mansor; Suppiah Nichiappan (Nadwa: Jurnal Pendidikan Islam, 2019)
The aim of study was to understand about the implementation of role of kuttab al fatih (KAF) philosophy in islamic character education. This research used qualitative method. The study revealed that the KAF philosophies are "the faith before the Quran” “the adab before the knowledge" and “the knowledge before the actions (‘amal), which are believed to aid KAF to achieve its vision and mission. The implementation of KAF Philosophies in Islamic character education creates a solid foundation of faith which contains basic values for students who contain character good personalities such as obedient, responsible, disciplined, hard-working, long term concentration or focus, away from prohibitions, vices, sincere, be grateful, and motivated because of Allah. KAF philosophies delivered to all parties in KAF included students, parents, teachers, management, staff Foundation, cleaning service and driver. AbstrakTujuan dari penelitian ini adalah untuk memahami tentang implementasi peran filosofi kuttab al fatih dalam pendidikan karakter Islami. Penelitian ini menggunakan metode kualitatif. Studi ini mengungkapkan bahwa filosofi KAF adalah "Iman sebelum Quran" "Adab sebelum Ilmu""Ilmu sebelum tindakan (amal), yang diyakini membantu KAF untuk mencapai visi dan misinya. Penerapan KAF Philosophies dalam pendidikan karakter Islam menciptakan fondasi iman yang solid yang berisi nilai-nilai dasar bagi siswa yang mengandung karakter kepribadian yang baik seperti taat, bertanggungjawab, disiplin, pekerja keras, konsentrasi atau fokus jangka panjang, jauh dari larangan, kejahatan, tulus, bersyukur, dan termotivasi karena Allah. Filosofi KAF disampaikan kepada semua pihak di KAF termasuk siswa, orang tua, guru, manajemen, staf Yayasan, layanan kebersihan dan sopir.